Governance and Social Responsibility: Palestinian Investment Fund - Awwad, Bahaa Subhi; Alkababji, Majdi Wael; Zidan, Shatha (Business and Economic Research, 2023)
<span style="color: #000000; font-family: Verdana, Arial, Helvetica, sans-serif; font-size: 10px; font-style: normal; font-variant-ligatures: normal; font-variant-caps: normal; font-weight: 400; letter-spacing: normal; orphans: 2; text-align: start; text-indent: 0px; text-transform: none; widows: 2; word-spacing: 0px; -webkit-text-stroke-width: 0px; white-space: normal; background-color: #ffffff; text-decoration-thickness: initial; text-decoration-style: initial; text-decoration-color: initial; display: inline !important; float: none;">The study aimed to assess the influence of corporate governance on social responsibility, applied on the Palestinian Investment Fund. The study utilized a quantitative analytical approach and gathered essential data from the Investment Fund's annual financial reports spanning the period from 2006 to 2020, available on its official website. The content analysis method, employing a checklist for measuring the social responsibility disclosure index, was applied to the annual financial reports. Data processing was carried out using SATAA. The study's findings revealed that corporate governance, particularly in its dimensions of board size, double CEO, independence, and gender diversity, significantly impacted social responsibility across dimensions combined, including society, environment, employees, customers, and the quality of service. However, the educational background dimension did not exhibit a notable effect on social responsibility. As a result of the research, it was recommended that organizations conduct annual assessments of corporate governance performance, making comparisons with previous years. Moreover, institutions were advised to provide comprehensive financial statements along with complementary explanations. This practice is deemed crucial for decision-makers and stakeholders, enabling them to obtain a clear understanding of the organization's status and system concerning various aspects of social responsibility and corporate governance.